The Application of Educaplay Games as a Digital-Based Tahsin Learning Medium in Elementary Schools: English - Desika Handayani (Universitas Persatuan Guru 1945 NTT, 2026)
The purpose of this study is to study how the Educaplay game-based learning media is applied in tahsin learning in elementary schools. The ADDIE model's research and development (R&D) methods are used in this study, and involve steps such as analysis, design, development, application, and evaluation. This study produces interactive and effective learning media. The results of the study show that using Educaplay can increase students' interest, activeness, and learning outcomes, especially in understanding the recitation of the Qur'an and basic tahsin materials. Additionally, teachers who receive training and technical support can use these mediums successfully, which makes learning more fun, interactive, and supports students' independent learning. In addition, this study shows that game-based learning media has the ability to overcome boredom caused by conventional approaches and can also significantly increase students' motivation to learn. Positive impact on students, this study shows that teachers must be prepared to manage game-based learning, including learning process management and technical abilities.